PRELIMINARY ANALYSIS OF THE INFLUENCE OF CHANGING DISTANCE BETWEEN PILES ON HORIZONTAL ACCELERATION ELASTIC RESPONSE SPECTRA FOR PILE-SUPPORTED STRUCTURE - Miladinović, Borko; Jeremić, Boris; Tomanović, Zvonko (Journal of Applied Engineering Science, 2024)
In the professional literature, the seismic load of pile-supported structure is divided into kinematic seismic load and inertial seismic load from superstructure. Due to the deficiencies in the legal framework in Montenegro (standard MEST EN 1998 - official Montenegrin counterpart of the European seismic standard Eurocode 8), civil engineers when defining seismic load of the pile-supported structure in practice almost every time treat only inertial seismic load from superstructure. Except the problematic neglect of the kinematic seismic load, the way in which the inertial seismic load is defined is also problematic. Due to the deficiencies in the legal framework not only in our country but also worldwide, civil engineers for defining the inertial seismic load of pile-supported structures in practice use elastic and design (inelastic) acceleration response spectra, which are prescribed generally for structures neglecting type of their foundations. This is rather rough and unrealistic assumption. This paper presents part of the results of 2D dynamic analyses of soil-pile-structure interaction, which were performed using the modern Domain Reduction Method, with the aim of preliminary investigating the seismic response of buildings founded on piles. In particular, the presented results show how changing distance between piles affects to the horizontal acceleration elastic response spectra at the base level of analysed pile-supported RC frame. In this way, pile foundation characteristics influence on the intensity of the superstructure seismic load is indirectly analysed. As expected, preliminary analyses have shown that in case of small distance between the piles (2d or 3d), this influence can be very significant. In this specific case, when the piles at the lower end are fixed in the bedrock, that influence is favourable because smaller elastic spectral accelerations are obtained for the complete range of periods (less seismic load of the superstructure). Of course, for some general conclusions and proposals, it is necessary to perform a significantly larger number of dynamic analyses with different configurations and characteristics of the soil-piles-structure system and seismic excitations. It is planned for the next period.